Upaya Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Quantum Teaching Mengenai Sistem Ekskresi - Lena Suwartini; Caswita Caswita (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
This research was structured with the aim of improving student learning outcomes through quantum teaching learning regarding the excretory system in science learning in Class VIII-E students of SMP Negeri 20 Tasikmalaya. This type of research is Classroom Action Research (CAR), in which the teacher is the executor of learning while the researcher is the observer. The research design uses the Kemmis and Mc. Taggart. This research was conducted in the even semester of the 2021/2022 school year, namely in March. The subjects of this study were students of Class VIII-E at SMP Negeri 20 Tasikmalaya which consisted of 33 students. The object of research is the active learning of students. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed that there was an increase in the active learning of students, namely in the first cycle an average of 74 (good category) and in the second cycle 81 (very good category), meaning that the learning outcomes in cycle II had fulfilled the Minimum Completeness Criteria of 75. This means there was an increase of 9.54%. Thus the use of the quantum teaching learning model regarding the excretory system in science learning can increase the learning activity of Class VIII-E students of SMP Negeri 20 Tasikmalaya.